Diversidade fenotípica e genotípica em isolados vaginais da levedura Candida glabrata - Nakamura, Sandra Sayuri (2012)
Over the last few years there has been an increase in the number of fungal infections affecting different sites in human including the vulvovaginal candidiasis (VVC) that is an infection of vulva and vagina affecting 25% of woman. It is estimated that 75% of women will have at least one episode of fungal vaginitis. Candida albicans is the most common species, but it has been increasing the incidence of VVC by non-albicans Candida, especially C. albicans. Moreover there has been observed an increase in the incidence of vulvovaginal candidiasis in non-albicans Candida species. C. glabrata is little known except by their innate resistance to azoles. In this scenario the objective of this study was the genotypic evaluation and the analysis of some virulence factors in C. glabrata isolated from VVC. We analyzed 60 isolates of C. glabrata which are maintained in a bank of yeasts at Universidade Estadual de Maringa, Maringa, Parana. For the genotypic characterization was used the PCR-RAPD assay by using the primers OPA18, P4 and OPE18, which showed a good similarity index. It was not found correlation between the analyzed virulence factors as well there was no genotypic grouping of relevance. The other hand, the diversity of the results was highlighted, suggesting an expressive phenotypic and genotypic plasticity of C. glabrata isolated from VVC. That characteristic, which was not related until the present, might reflect the high capacity of adaptation of this specie to different selective pressure and it probably can justify the increase of its incidence.